An Econometric analysis of the causes of deforestation of Southeast Asian countries - KHAING, Thandar (KDI School, 2017)
The development of Southeast Asian region is mainly depending on natural forest resources which are important not only in production of wood and other wood related products but also in conserving global environment. And then forests in the region provide employment to people in manufacturing wood based forest products or value added forest products and in managing the forest areas and in establishing plantations. Due to the above advantages, forest conservation and protection is important not only in the region but also all over the world. Southeast Asia’ deforestation and forest degradation rates were projected to be approximately two times of the rates of Latin America or tropical Africa (Mayaux et al., 2005). Knowing direct and indirect causes of deforestation is one of the best ways to reduce it. The objective of this thesis is to identify the serious drivers of deforestation in the Southeast Asian region. This study examined the most serious responsible drivers or causes of deforestation among arable land, permanent agricultural land, round wood production, fuelwood production, annual population, per capita GDP - Gross Domestic Products (constant at 2005) and planted forest areas (plantations). Southeast Asia eight countries (Cambodia, Indonesia, Lao People´s Democratic Republic, Malaysia, Myanmar, Philippines, Thailand and Vietnam) were conducted 1991 to 2014 (24 years). Panel data fixed effects model was conducted with three approaches. After conducting regression model in three approaches, the most serious driver is expansion of permanent agricultural land and arable land expansion follows it. Fuelwood production and planted forest areas (plantations) are fourth and fifth drivers of deforestation respectively. Round wood production is only statistically significant in the second approach so it is not a serious driver by comparing other variables (drivers of deforestation) used in the model. In the region, per capita GDP (constant at 2005) as economic indicator contribute the forest cover with positive ways (reduce the rate of deforestation).
Thesis(Master) --KDI School:Master of Public Policy,2017